Identification of the Niacin-Blunted Subgroup of Schizophrenia Patients from Mood Disorders and Healthy Individuals in Chinese Population - Sun, Liya (Schizophr Bull, 2018)
Schizophrenia (SZ) is a devastating mental disease caused by complex genetic and environmental factors. The pathological process and clinical manifestation of SZ are heterogeneous among patients, which hampers precise diagnosis and treatment of the disease. Since no objective marker for SZ has been established today, to identify a subgroup of the patients with homogeneous biochemical traits will provide a new angle for both researchers and clinicians to understand and manage the disease. In this study, we employed the niacin skin-flushing test in Chinese population and confirmed a niacin-blunted subgroup of SZ patients distinguishable from mood disorders (MD) and normal individuals. This subgroup accounted for 30.67% of the total SZ patients with a specificity of 88.37% in male subjects and 83.75% in female subjects. We support the notion that bluntness in niacin skin test might reflect abnormalities in membrane fatty acid composition, which could be induced by increased PLA(2) enzyme activity, in vivo oxidative stress or lipid metabolism imbalance in SZ. Further studies are encouraged to clarify the molecular origins of niacin-bluntness in SZ, which would provide extra clues for etiological research in schizophrenia and for new targeted treatment.